RED BULL: the Long term Business Sustainable Plan - Dhanasarnsombati, Tas (2011)
According to number of studies shows that food and beverage market is one of the most sustainable markets of them all. As majority of super-power supermarkets continue to increase their profits, proven that despite either the up or down-turn of the economic situations, food and beverage always will be the basic need to everyone. However with the food and beverage products keep emerging though out rapidly into the market, leaving consumers with numbers of choices to choose to purchase. In the fearsome and crowned markets as food and beverage market, it seems that all the business strategies, marketing plan, and pricing, are the key factors to indicate whether the products will be success or not. Furthermore even though the majority of food and beverage products are ‘necessary’ for human life, but some food and beverage products are exempted as ‘necessary products’ for some consumers. This paper will attempt to investigate the not so ‘necessary’ beverage market such as ‘Energy drink’. The focus case example chosen is ‘Red Bull’ which will include the analysis on future of ‘Red Bull’ business and lastly the recommendations of possibility expanding its product lines.